Frege’s unification - Boddy, Rachel (Proceedings of the Amsterdam Colloquium, 2025)
The purpose of this paper is to examine Frege’s views about the scientific unification of logic and arithmetic. In my view, what interpreters have failed to appreciate is that logicism is a project of unification, not reduction. The notion of unification, I argue, is especially helpful in clarifying how Frege views the projects of Grundlagen and Grundgesetze, and the differing role of definitions in these works. This allows us to see that there are two types of definition at play in Frege’s logicist works. I further use the notion of unification to offer an interpretation of Frege’s notion of fruitful definition, which, I think, helps clarify how the two types of definition relate, and how Frege uses them to ground the unification of logic and arithmetic.